2015
DOI: 10.5350/dajpn2015280207
|View full text |Cite
|
Sign up to set email alerts
|

Burden and burden-related features in caregivers of schizophrenia patients

Abstract: Burden and burden-related features in caregivers of schizophrenia patientsObjective: Burden, social support and coping methods in caregivers of patients and the relationship between these variables were cross-sectionally evaluated in this study.Method: Demographic form, Zarit Caregiver Burden Scale, Multidimensional Scale of Perceived Social Support and Ways of Coping Inventory were administered to the caregivers. The correlation of specified load levels with respect to the disease and characteristics of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
4
18
0
1
Order By: Relevance
“…59 In a similar study conducted by Ozlu et al to investigate illness induced burden, social support, coping methods, and the correlation between these variables in the caregivers of people with a diagnosis of schizophrenia, it was determined that, as the caregivers' burden increased, helpless and fatalistic approaches among the emotionfocused approaches for coping with stress increased. 60 The results obtained from the other studies are in line with the results of this study.…”
Section: Ta B L Esupporting
confidence: 91%
“…59 In a similar study conducted by Ozlu et al to investigate illness induced burden, social support, coping methods, and the correlation between these variables in the caregivers of people with a diagnosis of schizophrenia, it was determined that, as the caregivers' burden increased, helpless and fatalistic approaches among the emotionfocused approaches for coping with stress increased. 60 The results obtained from the other studies are in line with the results of this study.…”
Section: Ta B L Esupporting
confidence: 91%
“…Caregivers are also likely to experience constraints in social activities due to the stigma associated with mental illness that can further their social isolation (Kuipers et al, 1989). Several studies worldwide have reported high levels of burden experienced by caregivers of people with schizophrenia (Adeosun, 2013;Gutie´rrez-Maldonado et al, 2005;Mitsonis et al, 2012;Ozlu et al, 2015). Similar findings have also been attested by researchers from India (Gururaj et al, 2008;Jagannathan et al, 2014;Kate et al, 2013).…”
mentioning
confidence: 66%
“…The Zarit Family Burden Assessment Scale was developed by Martin 17 and adapted to Turkish by Ozlu et al 18 High scores indicate high family burden. Telepsychiatric follow-up of caregivers was carried out with the Follow-Up by Phone Form for Caregivers of Schizophrenic Patients.…”
Section: Methodsmentioning
confidence: 99%